Efficiency in learning : evidence-based guidelines to manage cognitive load - Clark, Ruth Colvin (Pfeiffer essential resources for training and HR professionals., 2006)
"Efficiency in Learning offers a road map of the most effective ways to use the three fundamental communication of training: visuals, written text, and audio. Regardless of how you are delivering your training materials--in the classroom, in print, by synchronous or asynchronous media--the book's methods are easily applied to your lesson presentations, handouts, reference guides, or e-learning screens. Designed to be a down-to-earth resource for all instructional professionals, Efficiency in Learning's guidelines are clearly illustrated with real-world examples"--Resource description page